Preparation of N-Graphdiyne Nanosheets at Liquid/Liquid Interface for Photocatalytic NADH Regeneration - Pan, Q.; Liu, H.; Zhao, Y.; Chen, S.; Xue, B.; Kan, X.; Huang, X.; Liu, Jian; Li, Z. (American Chemical Society, 2019)
Two-dimensional (2D) N-graphdiyne (N-GDY) nanosheets containing different number of N were synthesized by polymerization of triazine, pyrazine, and pyridine-based monomers at liquid/liquid interface. The configurations and nanostructures of N-GDY were well-characterized. The wettability changed to more hydrophilic as the N contents increased. The collected N-GDY was further employed as metal-free photocatalyst for NADH regeneration. The catalytic performance was related with the N content in the graphdiyne. The N3-GDY demonstrated the best activity. This strategy provided a new promising platform of designing unique 2D N-GDY with tunable performance in biorelated catalysis.